2021
DOI: 10.3390/pathogens10101322
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Impaired Polyamine Transport on Pneumococcal Transcriptome

Abstract: Infections due to Streptococcus pneumoniae, a commensal in the nasopharynx, still claim a significant number of lives worldwide. Genome plasticity, antibiotic resistance, and limited serotype coverage of the available polysaccharide-based conjugate vaccines confounds therapeutic interventions to limit the spread of this pathogen. Pathogenic mechanisms that allow successful adaption and persistence in the host could be potential innovative therapeutic targets. Polyamines are ubiquitous polycationic molecules th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…Metabolomics studies support the notion that polyamines could exert control over capsule synthesis at the transcriptional level [18]. Deletion of the polyamines transport operon (∆potABCD) resulted in a noticeable decrease in intracellular polyamine levels [19] and an increase in susceptibility to oxidative and nitrosative stress [20]. Similar to the SP_0916 deletion, there was an upregulation in the expression of genes associated with the PPP and the arginine deiminase system as an adaptive mechanism to manage stress conditions in ∆potABCD [20].…”
Section: Introductionmentioning
confidence: 72%
“…Metabolomics studies support the notion that polyamines could exert control over capsule synthesis at the transcriptional level [18]. Deletion of the polyamines transport operon (∆potABCD) resulted in a noticeable decrease in intracellular polyamine levels [19] and an increase in susceptibility to oxidative and nitrosative stress [20]. Similar to the SP_0916 deletion, there was an upregulation in the expression of genes associated with the PPP and the arginine deiminase system as an adaptive mechanism to manage stress conditions in ∆potABCD [20].…”
Section: Introductionmentioning
confidence: 72%
“…The potABCD mutant exhibits heightened vulnerability to oxidative stress, akin to the cadA mutant, due to a notable decline in polyamine and trehalose levels, which serve as antioxidants. Metabolomics analysis further elucidated that the potABCD mutant displays diminished glutathione levels, providing additional evidence to support its observed phenotype ( Nakamya et al, 2021 ).…”
Section: Polyamine Metabolismmentioning
confidence: 86%
“…Transcriptomic and proteomic analysis determined that this mutation negatively affects the expression of various genes known to be essential for OSR, including tpxD and htrA . Additionally, the authors propose that SpeA not only regulates the synthesis of glutathione but also influences the endogenous production of H 2 O 2 ( Nakamya et al, 2021 ). The speA mutation also leads to an increase in carbon flow through the pentose phosphate pathway (PPP), which is considered a cellular response to oxidative stress.…”
Section: Polyamine Metabolismmentioning
confidence: 99%
“…Glucose is preferentially catabolized by the glycolysis pathway and to a minor extent by PPP in S. suis , which mainly provides intermediates needed for anabolic reactions ( Willenborg et al., 2015 ). The metabolic shift toward the PPP and reduced amino acid production usually represent the cellular responses to increased stresses ( Nakamya et al., 2021 ). Increased activity of the PPP will reduce the energy-consumption through the glycolysis pathway and rapidly meet the cellular demand for NADH/NADPH to combat oxidative stress ( Nakamya et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic shift toward the PPP and reduced amino acid production usually represent the cellular responses to increased stresses ( Nakamya et al., 2021 ). Increased activity of the PPP will reduce the energy-consumption through the glycolysis pathway and rapidly meet the cellular demand for NADH/NADPH to combat oxidative stress ( Nakamya et al., 2021 ). Our data showed that the central metabolism shifts from the glycolysis pathway toward the PPP in S. suis after glycogen induction ( Figure 3 ) and presents the possible stress responses of S. suis under glycogen-induced conditions.…”
Section: Discussionmentioning
confidence: 99%